Tradisi Ziarah Kubur Pasca Pernikahan (Studi Kasus Kelurahan Manisa, Kecamatan Baranti, Kabupaten Sidrap, Sulawesi Selatan) - Syandri; Iskandar; Sulaiman Kadir (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This study aimed to identify the process and purpose of the grave pilgrimage tradition after marriage in Manisa village, Baranti subdisctrict, Sidrap district, South Sulawesi, and also to examine the law of the custom in the view of Islamic law. This research employed a qualitative approach with the field study method (Field Research) and library research. The study shows that: 1. People ini Manisa village after celebrating their wedding they make grave pilgrimage in forms of such as: Determining a certain time according to the agreement of the bride and groom, preparing the necessary preparations such as water, kettles, and pandanus leaves, making ablution before going to the graveyard, praying before entering the cemetery, watering the grave with water mixed with pandanus leaves, holding the gravestone, praying for the late by reciting certain chapters finalized by surah Al-Fatihah. 2. Grave pilgrimage is one of the prescribed acts of worship but it should be in accordance with the guidance of the Prophet. As for what is found in the people of Manisa Urban Village, there are still a number of differences between what they do and what had been exemplified by the Messenger of Allah such as the determination of a special time for the grave pilgrimage, watering the grave, and seeking for blessing from the graves visited.